GAMBARAN HISTOPATOLOGI ARTERI KORONARIA TIKUS PUTIH JANTAN GALUR WISTAR SETELAH PEMBERIAN DIET ATEROGENIK SELAMA DELAPAN MINGGU - Neneng Mutiara Sari; Enikarmila Asni; Zulkifli Malik (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2015)
ABSTRACTAtherosclerosis could be induced by feeding rats aterogenik dietcontaining high cholesterol and colic acid. For increasing atherosclerosis processvitamin D3 also given orally. Aim this research has an aims to analyze thedifference of coronary artery histopathologycal image between white rat strainwistar feeding by aterogenic diet and standard diet for 8 weeks. This is anexperimental laboratory research with post test only design. This research usedtwelve rats were segregated into two groups (n=6) labeled ads control; fedstandard diet and atherogenik fed diet ( containing colic acid 0,2%, fat 5%, andyolk 2%) and vitamin D3. The statistic test result do not show a significantdifference of atherogenic score of control group and atherogenic group. As theconclusion, feeding atherogenic diet for 8 weeks can induce the formation ofaccumulation of extracellular lipid in all samples of coronary artery of white rats,atheroma in 3 samples and thrombus 1 samples, while feeding standard diet justso atherosclerosis process on 4 samples, the formation of accumulation ofintracellular lipid in 1 samples and atheroma in 3 sample.Keywords : atherosclerosis, histopathology, atherogenic diet